Nitric Oxide Reactivity with Globins as Investigated Through Computer Simulation - Marti, Marcelo A. (2008)
This chapter reviews the application of classical and quantum-mechanical atomistic simulation tools used in the investigation of several relevant issues in nitric oxide reactivity with globins and presents different simulation strategies based on classical force fields: standard molecular dynamics, essential dynamics, umbrella sampling, multiple steering molecular dynamics, and a novel technique for exploring the protein energy landscape. It also presents hybrid quantum-classical schemes as a tool to obtain relevant information regarding binding energies and chemical reactivity of globins. As illustrative examples, investigations of the structural flexibility, ligand migration profiles, oxygen affinity, and reactivity toward nitric oxide of truncated hemoglobin N of Mycobacterium tuberculosis are presented.